The french policy of foreign intervention from 2007 to 2017 - (:unkn) unknown (My University, 2018)
This thesis is divided into three main parts. The first one underlines the different factors which contribute to the continuity of French politics of military intervention, stressing the notion of middle power, French culture of human rights and the very special link which still unites nowadays Paris to the African continent. The second part examines the evolution of international norms and UN practice and tries to appreciate the part of the Security Council in the establishment of the French foreign policy. This section includes a comparative dimension as it deals with American, European, Russian and emerging countries politics in terms of military interventions. That focus enables to grasp French specific features, both institutional and in terms of military capacities. The last part of this work aims at analyzing the different military fields of the French army during the last decade. In Africa, military operations are often led unilaterally, African troops then taking over gradually. In the Middle East, French military interventions are mostly part of international coalitions led by the United States. "Opération Harmattan" in Libya is addressed in a proper section as it is in between the classical military interventions in Africa and the one we use to observe in the Middle East. Initiated by France and the UK but conducted under NATO leadership, this intervention constitutes a paradigm shift in French, European and Transatlantic security. This thesis thus analyzes a decade of French military engagement and enables to interpret the current events regarding crisis management and conflicts.
Keywords: African Research